Translating the rhetoric of the 2030 agenda into reality: roles of the counselling psychologists (2019)
In order to turn the bold dreams and ground-breaking ambition of the 2030 agenda into tangible results and to "meet the needs of the present Nigerians without compromising the ability of future generations to meet their own needs", this paper proposes that counselling services are sine qua non. This stance is premised on the fact that counselling has well documented evidence in assisting individuals to take the right decision or choose a course of action that will benefit all and sundry. Specifically, the paper recommended four major roadmaps for localizing the Sustainable Development Goals, namely; (i) provision of career counselling services (ii) utilising evidence-based practices for recruitment and placement (iii) prevention of human and material wastages traceable to youth restiveness (iv) and last but not least, is changing Mindset (cognitive restructuring) for actualization of SDGs. It concluded that in order to translate the rhetoric of the 2030 agenda into reality there is need to step beyond traditional approaches and consider strategies that are evidence informed and innovative. One of the strategies is to give counselling services prominence in every sector of the economy because it has the capacity of shaping the personal, social, career and emotional behaviours of individuals for optimal performance in every sphere of life.